Pengaruh Kebiasaan Bermain Game Online Terhadap Hasil Belas Siswa Kelas Tinggi SDN 26 Watang Palakka - Astuti Astuti; satriani satriani; Abd Hafid (Universitas Negeri Makassar, 2021)
The problem in this study is the habit of students in playing online games so that it will have an impact on student learning outcomes if they cannot manage time to study and time to play online games. This study is a quantitative study with a correlation design that aims to determine the effect of online game playing habits on the learning outcomes of high-class students at SDN 26 Watang Palakka. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis, it was obtained that the habit of playing online games had an average of 84 and a percentage of 84% with a very good category and the average student learning outcomes had an average of 83,670 and a percentage of 83,670% with a very good category. Then based on the results of inferential statistical analysis, the tcount value (5.858) is greater (>) the ttable value (1.66277) at the 5% significance level. Thus, H0 is rejected and H1 is accepted, so it can be concluded that there is a significant influence between the habit of playing online games on the learning outcomes of high-class students at SDN 26 Watang Palakka. So the more students have high self-control, are able to manage time to play online games and time to study, student learning outcomes will increase.